Long-term glycine propionyl-l-carnitine supplemention and paradoxical effects on repeated anaerobic sprint performance - Jacobs, P. L.; Goldstein, E. R. (Journal of the International Society of Sports Nutrition, 2010)
It has been demonstrated that acute GPLC supplementation produces enhanced anaerobic work capacity with reduced lactate production in resistance trained males. However, it is not known what effects chronic GPLC supplementation has on anaerobic performances or lactate clearance.